Integration of Thematic Interpretation and Physiology of Prayer Movements: An Interdisciplinary Study of Surah Al-Tin and Musculoskeletal Balance - Lusi Ismayenti (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Prayer, as a fundamental act of worship in Islam, not only has spiritual value but also contains physiological dimensions that have the potential to improve musculoskeletal health. The urgency of this research lies in the need for an interdisciplinary approach that integrates thematic interpretation of the Qur'an with physiological science to understand the relationship between the spiritual dimension and human body balance. This article aims to examine the relationship between the concept of